Hemidystonia improved by intrathecal baclofen infusion therapy: A case report - Takashi Asahi; Kiyonobu Ikeda; Shiro Horisawa; Taku Nonaka; Yuko Muro; Nobutaka Yamamoto; Takaomi Taira (Interdisciplinary Neurosurgery)
Intrathecal baclofen therapy (ITB) is a well-established treatment for limb spasticity due to brain and spinal cord disorders, and it is also indicated for dystonia, though mainly reported in generalized or pediatric cases. This report highlights a 46-year-old male with hemidystonia from writer’s cramp. Diagnosed at age 30, his symptoms persisted despite oral medications, botulinum toxin injections, and deep brain stimulation targeting the left thalamus ventro-oral nucleus and globus pallidus internus. Two years later, his symptoms worsened and extended to the right side. At our clinic, a baclofen screening test significantly reduced muscle tone, enabling writing. Following the implantation of a baclofen pump, his dystonia markedly improved, restoring his writing ability. This case supports considering ITB for patients with severe, refractory dystonia and muscle hypertonus, even in cases without generalized dystonia.